2020
DOI: 10.1007/s00205-020-01584-6
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of Symmetric Domain Walls for the Bénard–Rayleigh Convection Problem

Abstract: We prove the existence of domain walls for the Bénard-Rayleigh convection problem. Our approach relies upon a spatial dynamics formulation of the hydrodynamic problem, a center manifold reduction, and a normal form analysis of a reduced system. Domain walls are constructed as heteroclinic orbits of this reduced system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Domain walls, or grain boundaries, are line defects which may occur between rolls with different orientations (see Figure 1.1), and are steady solutions of the system (1.1)- (1.3). In our previous work [5], we showed that symmetric domain walls bifurcate for the Navier-Stokes-Boussinesq system (1.1)-(1.3) with either "rigid-rigid" or "free-free" boundary conditions for Rayleigh numbers R > R c close to the critical value R c . These domain walls are solutions of the steady system which are periodic in y, symmetric in x and their limits as x → ∓∞ are rolls rotated by opposite angles ±α with α ∈ (0, π/3).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Domain walls, or grain boundaries, are line defects which may occur between rolls with different orientations (see Figure 1.1), and are steady solutions of the system (1.1)- (1.3). In our previous work [5], we showed that symmetric domain walls bifurcate for the Navier-Stokes-Boussinesq system (1.1)-(1.3) with either "rigid-rigid" or "free-free" boundary conditions for Rayleigh numbers R > R c close to the critical value R c . These domain walls are solutions of the steady system which are periodic in y, symmetric in x and their limits as x → ∓∞ are rolls rotated by opposite angles ±α with α ∈ (0, π/3).…”
Section: Introductionmentioning
confidence: 95%
“…For the analysis of the bifurcation problem we use the spatial dynamics approach developed for the Swift-Hohenberg equation in [6] and adapted to the Navier-Stokes-Boussinesq system (1.1)-(1.3) in [5]. The steady system (1.1)-(1.3) is written as a dynamical system in which the evolutionary variable is the spatial variable x and a center manifold theorem is used to reduce this infinite dimensional dynamical system to a 12-dimensional system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations